2011
DOI: 10.4103/0019-5154.82479
|View full text |Cite|
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with psoriasis in cases from the Nile Delta of Egypt

Abstract: Background:Psoriasis is a chronic inflammatory skin disease with an immunogenetic background. This work was planned to check for the association of polymorphisms related to cytokine genes TNF-α-308 (G/A), IL-10-1082 (G/A), IL-6-174 (G/C), and IL-1Ra (VNTR) with psoriasis in cases from Egypt.Materials and Methods:This work included 46 cases with psoriasis recruited from the Dermatology Departments, University Hospitals, Nile Delta region of Egypt. They included 14 males and 32 females with an age mean ± SD of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
4
23
2
Order By: Relevance
“…[54][55][56] Therefore, many genetic studies were conducted to investigate the correlation of IL-10 gene polymorphisms with various immune-mediated diseases. IL-10 -1082 A/G and its association with various diseases were the only studied SNP in Egyptian population such as psoriasis, 57 HBV, 58 Behcet's disease (BD), 59 and various types of tumors. 37,60 Haplotype frequencies are shown for each level of control and IBC group.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] Therefore, many genetic studies were conducted to investigate the correlation of IL-10 gene polymorphisms with various immune-mediated diseases. IL-10 -1082 A/G and its association with various diseases were the only studied SNP in Egyptian population such as psoriasis, 57 HBV, 58 Behcet's disease (BD), 59 and various types of tumors. 37,60 Haplotype frequencies are shown for each level of control and IBC group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that certain genotypes of cytokine gene polymorphisms are more predominant in psoriatic cases with moderate severity (Settin et al, 2009). This particular finding suggests that certain genetic variations may be considered as severity-modifying polymorphisms with respect to psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is considered an attractive candidate gene based on its chromosomal location and functional relevance. A number of studies have examined the association between IL-10 polymorphisms and psoriasis, but reported results are contradictory [10][11][12][13][14][15][16][17], possibly because of the low statistical powers of individual studies. Therefore, in order to overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false-positive or -negative associations [18][19][20], we turned to meta-analysis.…”
Section: Introductionmentioning
confidence: 99%